Parametric Study of TLPs Subjected to Random Waves - Kurian, V.J.; M.A, Gasim; Sambu Potty, Narayanan; VALLYUTHAM, Kalaikumar (2008)

(untitled)
TLP technology preserves many of the operational advantages of a fixed platform while reducing the cost of production in deep water. The amplitudes of motion must be sufficiently small to prevent flexural yielding of the drilling risers which connect the platform to the sea bed template. In this paper, a MATLAB computer program has been developed for determining the dynamic responses of square TLPs subjected to regular and random waves. The structure has been considered as a rigid body and all the six motions as well as tether tensions have been determined. Linear Airy wave theory and Morison equation have been used for wave force calculations. Newmark Beta method of time domain analysis has been used. The response amplitude operators for the motions of a typical TLP have been compared with available theoretical and experimental results. Also, parametric studies have been made varying parameters such as water depth, pretension, wave angle and position of center of gravity (CG). The results highlight the variation in platform responses caused by changing these parameters.